PERSEPSI ATAS BERLAKUNYA PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 - Irmia, Rochimatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Every year micro, small, and medium enterprises in Indonesia undergo significant development. When it is seenfrom its structures, the Indonesian Economy is still supported by micro, small, and medium enterprises(UMKM). Micro, small, and medium enterprises (UMKM) not only have become the main priority in economybut it also has become the hope of ongoing development in Indonesia. The government is keep on trying thedevelopment of micro, small, and medium enterprises by issuing people business credit program and new taxregulation that is the Government Regulation no. 46 of 2013 which is in effect in July 2013. The purpose of thisresearch is to find out what perception that arises on the enactment of Government Regulations no. 46 of 2013particularly for tax authorities and tax payers. The object of the research is tax income at Pratama Tax OfficeRungkut. Based on the result of research, it has been found that the state income in 2013 underwentimprovement. The new regulation that has been issued by the government gives additional income each month.This regulation is considered to be very easy to understand by the tax authorities, yet the comprehension oftaxpayers is considered to be low. The obligation that is incurred by taxpayers is considered to be too high thanthe previous one. This regulation provides convenience when it is considered from the calculation andpreparation of annual tax return.Keywords: Perception, Micro, Small, and Medium Enterprises (UMKM), Government Regulation No. 46of 2013.